Double edge-based traceback for wireless sensor networks. (2015) - Zhang, Zhiming; Li, Ping; Wu, Fuying; Deng, Jiangang
In some hostile environment, the sensor nodes can be captured by the adversary, the adversary can launch various attacks through the compromised nodes. In this paper, a double edge-based traceback (DETrace) scheme is proposed to reconstruct the attack path and locate the compromised source node, in the DETrace, each packet can be marked by four nodes, the base station can get most two edges of the attack path from one marked packet. In addition, to resist the compromised immediate forwarding nodes launch various attacks, the DETrace encrypts the marking information of packet during the process of transferring. The security and performance analysis show that the DETrace can resist mark re-ordering attack, altering mark attack and removing mark attack, and is much faster in convergence time; the simulation results show that the DETrace needs fewer marked packets to reconstruct the attack path and locate the attack source.